Study of craters formed on surface of AISI 321 stainless steel after high power ion-beam exposure; Vacuum; Vol. 198 - Zhidkov M. V. Mikhail; Legachyov A. E. Aleksandr Evgenjevich; Golosov E. V. Evgeny Vitaljevich; Gazizova M. Yu. Marina Yurjevna; Pavlov S. K. Sergey Konstantinovich; Remnev G. E. Gennady Efimovich (2022, 2022)
Title screen